2017
DOI: 10.1177/0031512517704340
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Responses and Session Ratings of Perceived Exertion to a Rugby Match and Fatigue Test

Abstract: This study compared the effects of an official rugby match and a fatigue test on the salivary cortisol responses of 13 rugby players. We also examined the relationship between this cortisol response and session ratings of perceived exertion (session-RPE). We collected saliva before and after the match and fatigue test and assessed physical effort intensity via session-RPE using a CR-10 scale. We measured cortisol concentration by enzyme-linked immunosorbent assays. Results were greater session-RPE and cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…Despite the high intensity reported and significant duration of the games, no differences were observed between pre- and post-cortisol concentrations for the whole group. These results do not agree with other studies in basketball, 11,26 rugby, 27 tennis, 10,28 and judo competitions 29,30 which state that increases in cortisol can be explained by the increase in the physiological demands of the competition measured through RPE 3,11,31 or HR. 3…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Despite the high intensity reported and significant duration of the games, no differences were observed between pre- and post-cortisol concentrations for the whole group. These results do not agree with other studies in basketball, 11,26 rugby, 27 tennis, 10,28 and judo competitions 29,30 which state that increases in cortisol can be explained by the increase in the physiological demands of the competition measured through RPE 3,11,31 or HR. 3…”
Section: Discussioncontrasting
confidence: 94%
“…Similar behavior has been observed in rugby athletes without disability; Caetano-Júnior et al. 27 reported reductions in cortisol concentrations in two athletes and Lindsay et al. 37 found different magnitudes of increased cortisol concentrations.…”
Section: Discussionsupporting
confidence: 61%
“…It was also demonstrated that decreases in the blood glucose concentration trigger the pituitary-adrenocortical axis to enhance secretion of ACTH and cortisol during prolonged exercise in humans [ 7 , 8 ]. Moreover, there were significant correlations between the cortisol response and the sense of fatigue during stressful exercise [ 9 , 10 ]. These reports point out that cortisol is released in response to glycogen depletion or reduced blood glucose levels to maintain the blood glucose level, delaying fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that prolonged exercise induced a decrease in blood glucose, which caused an increase in the sense of fatigue [1] and that carbohydrate supplementation postponed fatigue during exercise by maintaining blood glucose levels [2,3]. One of the glucocorticoid hormones, cortisol, which quickly increases during exercise [4,5], was reported to significantly correlate with the feeling of fatigue during exercise [6,7]. It was also reported that ammonia, which is produced by accelerating the catabolism of muscle proteins when energy is depleted during prolonged exercise, led to the feeling of fatigue through neurotoxic effects [8,9].…”
Section: Introductionmentioning
confidence: 99%